Visual Analog Scale as a Predictor of GINA-Defined Asthma Control. The SACRA Study in Japan. (June 2013) - Ohta, Ken; Jean Bousquet, Philippe; Akiyama, Kazuo; Adachi, Mitsuru; Ichinose, Masakazu; Ebisawa, Motohiro; Tamura, Gen; Nagai, Atsushi; Nishima, Sankei; Fukuda, Takeshi; Morikawa, Akihiro; Okamoto, Yoshitaka; et al.
<x xml:space="preserve">Abstract</x> Objective. The assessment of asthma control is pivotal to treatment decisions. A questionnaire that assesses the Global Initiative for Asthma (GINA)-defined control requires four questions. A visual analog scale (VAS) to evaluate asthma control can be simply marked, but its correlation with GINA-defined control has been insufficiently evaluated. The purpose of this study is to evaluate whether VAS levels can predict GINA-defined asthma control with particular emphasis on the distinctions between "partly controlled" and "uncontrolled" and between "partly controlled" and "controlled" asthma, Methods. A cross-sectional multicenter study was carried out throughout Japan (SACRA) from March to August 2009 among patients with a diagnosis and treatment of asthma. Asthma control was studied using the GINA questionnaire and a VAS measurement of asthma severity. Pulmonary function testing was not carried out, Results. 1910 physicians enrolled 29, 518 patients with asthma. 15, 051 (51.0%) questionnaires were administered by physicians; patients filled out 14, 076 (47.7%) questionnaires themselves. 28, 225 (95.6%) of the patients were evaluable. VAS measurement of asthma symptoms was useful in predicting levels of GINA-defined control categories (the area under the receiver operating characteristic curve ranging from 0.704 to 0.837). Patients with "controlled, " "partly controlled, " and "uncontrolled" asthma were discriminated by VAS levels (1.50, 4.79, and 7.19). Similar results have been obtained with self- and physician-administered questionnaires showing the validity of results. Conclusion. Measurement of VAS levels is able to discriminate between patients with "controlled, " "partly controlled, " and "uncontrolled" asthma. The VAS score could be a simple guide in clinical situations requiring daily or regular evaluation of asthma control.